Nation-Building, Identity and Citizenship Education
XIV, 198 p.
Keywords: This book examines issues surrounding the nation-building processes, and identity and citizenship education in the global culture, from various perspectives. Globally, there are increasing arguments both for the democratisation of education and for the use of education to promote a democratic society, based on equality, and social justice. It is argued that authentic and democratic schools could better prepare for active citizenship and for a strong civil society which are seen to be the foundation of a democratic state. The book critiques the dominant discourses and debates pertaining to cultural identity, set against the current climate of growing social stratification and unequal access to quality education for all. It opens discourses related to globalisation and the state, and approaches to constructing national, ethnic and religious identities in the global culture. It explores the ambivalent and problematic relationship between the state, globalisation and the construction of cultural identity.